1941
DOI: 10.1128/jb.41.4.447-455.1941
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characteristics of Bacteriophages for Staphylococci of Bovine Mastitis

Abstract: Although numerous reports on bacteriophages for staphylococci of human origin have appeared, none could be found regarding phages active against staphylococci from bovine sources. This laboratory has been concerned with various phases of bovine mastitis, hence it was of interest to investigate the occurrence and role of bacteriophage in staphylococcal mastitis. While this type of mastitis is probably not as prevalent as streptococcal mastitis, staphylococci do produce both acute and chronic forms of the diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1944
1944
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Bacteriophage can be used in animal husbandry as an additive therapy besides of infection management of antibiotic-resistant Staphylococcus spp. Slanetz and Jawetz [ 25 ] showed the presence of lytic staphylococcal bacteriophages from mastitic cow milks but suggested that these phages were not freely in milk, always linked to some particles. Gill et al .…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriophage can be used in animal husbandry as an additive therapy besides of infection management of antibiotic-resistant Staphylococcus spp. Slanetz and Jawetz [ 25 ] showed the presence of lytic staphylococcal bacteriophages from mastitic cow milks but suggested that these phages were not freely in milk, always linked to some particles. Gill et al .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the work has focused on screening raw milk samples obtained from a confirmed mastitis cattle, either directly after centrifuging and filtering of samples or via enrichment procedures to amplify and isolate phages [ 28 , 34 ]. Phages have been reported to actively bind to, lyse and amplify in milk constituents, and huge successes of phage isolation for S. aureus , S. agalactiae and S. arlettae have been recorded from this source through this method [ 7 , 28 , 29 , 34 , 40 , 41 , 46 , 49 , 63 ]. However, in one instance, no phage was isolated from the milk samples examined [ 48 ].…”
Section: The Case For Phage Therapy To Control Bovine Mastitismentioning
confidence: 99%
“…Phage typing of staphylococci from all the above-mentioned dairy sources has been reported (* Slanetz and Jawetz, 1941;Macdonald, 1946;*Smith, 1948a, b;Hauge, 1951Hauge, , 1952McLean, 1951;Price et nl., 1954;Asso, 1956;Barnum and Fuller, 1956;Rountree et al, 1956;Edwards and Rippon, 1957;*Nakagawa, 1958, l%Oa, b, c;*Seto and Wilson, 1958;*Coles and Eisenstark, 1959a, b,c;Hoffmann, 1959;Loken, 1959;*Malik and Singh, 1959;1960a, b;Mondini .and Dovadola, 1959;Mora and Cavrini, 1959;Papavassiliou and Obiger, 1959;Reid and Wilson, 1959;Hauslcr et al, 1960;Mondini and Gasparini, 1960a, b ;*Takagaki, 1960 ;Thorne and Wallmark, 1960;Clark et al, 1961;*Davidson, 1961a, b, c;Fratta et al, 1961 ;White and McDonald, 1961 ;McPhillips and Cunningham, 1962;St. George et al, 1962;*Slanetz and Bartlett, 1962).…”
Section: Strains Lysed By Phages Of Group IV [42d Arementioning
confidence: 99%